2010
DOI: 10.1007/s11701-010-0199-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of outcomes between laparotomy and robotic technique for cervical cancer

Abstract: We evaluated the results of patients who had undergone robotic-assisted radical hysterectomy or open radical hysterectomy for cervical cancer. The study included eight patients who had undergone robotic-assisted radical hysterectomy (group 1) and seven patients who had undergone radical hysterectomy (group 2). Demographic characteristics and operative results of all patients were compared. Body mass index, age, previous abdominal surgery, surgical procedure performed, total anesthesia duration, operation durat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…As of December 31, 2012, there were 2585 da Vinci ® Surgical Systems installed in approximately 2025 hospitals worldwide with approximately One of the first publications regarding robot-assisted hysterectomy was in 2006 by Reynolds [9]. Studies have shown that robot-assisted hysterectomy is associated with a reduction in estimated blood loss [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27], complication rates [10][11][12][13][14][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] and reduced length of stay but is associated with longer operating times [10][11][12][13][14][15][16][17][18]…”
Section: Introductionmentioning
confidence: 99%
“…As of December 31, 2012, there were 2585 da Vinci ® Surgical Systems installed in approximately 2025 hospitals worldwide with approximately One of the first publications regarding robot-assisted hysterectomy was in 2006 by Reynolds [9]. Studies have shown that robot-assisted hysterectomy is associated with a reduction in estimated blood loss [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27], complication rates [10][11][12][13][14][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] and reduced length of stay but is associated with longer operating times [10][11][12][13][14][15][16][17][18]…”
Section: Introductionmentioning
confidence: 99%